Unifying double flame spray pyrolysis with lanthanum doping to restrict cobalt–aluminate formation in Co/Al2O3 catalysts for the dry reforming of methane. Issue 18 (20th August 2019) - Horlyck, Jonathan; Pokhrel, Suman; Lovell, Emma; Bedford, Nicholas M.; Mädler, Lutz; Amal, Rose; Scott, Jason
Abstract : Atomic-sized lanthanum doping via double flame spray pyrolysis leads to remarkable dry reforming of methane performance. Abstract : Mixed cobalt–aluminium–lanthanum oxides were synthesised via double flame spray pyrolysis and evaluated as dry reforming of methane catalysts. The materials were doped with lanthanum loadings up to 15 wt% and synthesised at two separate nozzle distances to inhibit the formation of complex cobalt–aluminate (CoAl2 O4 ) spinels. Lanthanum content and the nozzle distance separating the flames were found to have a key influence over material composition and performance. The addition of La to the system gave rise to the substitution of single atom La 3+ into the Al2 O3 lattice at lower La loadings with aggregated La atoms appearing as the La loading increased, as shown by high-resolution transmission electron microscopy and XANES. Hydrogen temperature programmed reduction showed that doping with La and increasing the nozzle distance limited CoAl2 O4 spinel formation and facilitated the production of readily reduced Co species. The addition of La also resulted in an increased material basicity, independent of nozzle distance, lending the catalysts a strong resistance to carbon formation. Methane conversion and catalyst stability at 700 °C were enhanced via the addition of La. Maximum methane conversions of 89–93% were observed for the two samples with the greatest La content (15 wt%), with no sign of catalyst deactivation or carbon formation, making these promising materials for the dry reforming reaction.